2014
DOI: 10.2147/ijn.s56212
|View full text |Cite
|
Sign up to set email alerts
|

Acute toxicity of nickel nanoparticles in rats after intravenous injection

Abstract: This study was carried out to add scientific data in regard to the use of metallic nanoparticles in nanomedicine. The acute toxicity of nickel (Ni) nanoparticles (50 nm), intravenously injected through the dorsal penile vein of Sprague Dawley rats was evaluated in this study. Fourteen days after injection, Ni nanoparticles induced liver and spleen injury, lung inflammation, and caused cardiac toxicity. These results indicate that precautionary measures should be taken with regard to the use of Ni nanoparticles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(18 citation statements)
references
References 32 publications
2
16
0
Order By: Relevance
“…Cytotoxic effects were reported when exposed to materials containing nickel [3234]. Therefore, CS porous Nitinol with resistance to Ni leaching is crucial to its biocompatibility and use as implants.…”
Section: Resultsmentioning
confidence: 99%
“…Cytotoxic effects were reported when exposed to materials containing nickel [3234]. Therefore, CS porous Nitinol with resistance to Ni leaching is crucial to its biocompatibility and use as implants.…”
Section: Resultsmentioning
confidence: 99%
“…These findings are consistent with previous studies that found liver toxicity for cobalt, manganese, and nickel nanoparticles. 8, 45, 46 Liu et al also reported that exposure of BRL 3A rat derived liver cells to Co nanoparticles reduced cell viability and LDH release, which was accompanied by ROS generation and DNA damage. 45 Similar induction of LDH release was found for micron-size MnO 2 particles in the same liver cell line.…”
Section: Discussionmentioning
confidence: 96%
“…These changes may be because of the interference of the NPs in the process of erythropoiesis (Morsy, El-Ala, & Ali, 2016). Ni NPs significantly increased the WBC count in rats after intravenous administration (Magaye et al, 2014).…”
Section: Ni Biodistributionmentioning
confidence: 99%